Cost of unintended pregnancy in Norway: a role for long-acting reversible contraception. Issue 2 (23rd December 2014) - Henry, Nathaniel; Schlueter, Max; Lowin, Julia; Lekander, Ingrid; Filonenko, Anna; Trussell, James; Skjeldestad, Finn Egil
Abstract : Objectives: The objective of this study was to quantify the cost burden of unintended pregnancies (UPs) in Norway, and to estimate the proportion of costs due to imperfect contraceptive adherence. Potential cost savings that could arise from increased uptake of long-acting reversible contraception (LARC) were also investigated. Methods: An economic model was constructed to estimate the total number of UPs and associated costs in women aged 15–24 years. Adherence-related UP was estimated using 'perfect use' and 'typical use' contraceptive failure rates. Potential savings from increased use of LARC were projected by comparing current costs to projected costs following a 5% increase in LARC uptake. Results: Total costs from UP in women aged 15–24 years were estimated to be 164 million Norwegian Kroner (NOK), of which 81.7% were projected to be due to imperfect contraceptive adherence. A 5% increase in LARC uptake was estimated to generate cost savings of NOK 7.2 million in this group. Conclusions: The cost of UP in Norway is substantial, with a large proportion of this cost arising from imperfect contraceptive adherence. Increased LARC uptake may reduce the UP incidence and generate cost savings for both the health care payer and contraceptive user.